Police dog procedural - Diaz, Lena (Sydney, NSW : Harlequin Mills & Boon, 2022)
A child left on a doorstep...a K-9 officer and his partner determined to solve this mystery... When police lieutenant Macon Ridley and his loyal K-9, Bogie, respond to a frantic call from Daniels Canine Academy, they're stunned to discover a baby on DCA's doorstep. New recruit Macon tantalised Emma Daniels when she first trained his new pup. Now, that sizzling spark propels the pair to solve a dangerous mystery. At stake is not only an innocent infant, but also Emma herself.
"Celebrating Lena Diaz's 25th book" -- Cover screen.
Title from title screen.
Mode of access : Available online.
Keywords: Contemporary romance; Fiction - Mystery & Detective - Police Procedural; Electronic books; Romance fiction